Pudding up with murder - Buckley, Julia, 1964- (Buckley, Julia, 1964- Undercover dish mystery., 2017)
Customers trust Lilah Drake to keep her mouthwatering meals under wraps, but when a millionaire meets his untimely end, some sinister secrets become the main course ... Spring is right around the corner, and with the warmer temperatures come plenty of food requests from Lilah Drake's covered-dish clients. Lilah pulls out all the stops with a sweet new casserole for the birthday party of Marcus Cantwell, a wealthy curmudgeon who has some angry ex-wives and more than a few enemies. When he's found facedown in Lilah's casserole, it's anyone's guess as to who might have wanted the old man dead. A possible new heir to Marcus's fortune adds some unexpected spice to the investigation, but Lilah fears that the old adage is true, and "the proof is in the pudding."